Critical success factors for Learning Management Systems in higher education: A literature review - Otto , Sofie; Overgaard Markman, Anna; Svarre, Tanja (Proceedings of the International Conference on Networked Learning, 2024)
Learning Management Systems count as a core component in the orchestration of learning in higher education and is widely prevalent around the world. This paper identifies the factors that are critical for learning management systems to be successful for learners. A literature review including 14 research papers forms the empirical basis and DeLone & McLean’s (2003) model of IS success is used to map the papers. The papers focus on student users of implemented learning management systems, mainly studied through surveys. The analysis shows that ‘user satisfaction’ is most generally influenced by ‘information quality’ and ‘system quality’, while ‘net benefits’ is mostly influenced by ‘user satisfaction’. The papers have either focused less on ‘service quality’, ‘use’ and ‘intention to use’, or they have not been able to identify significant correlations based on these variables. The findings are related to the role of LMS as mandatory information systems and the implications for the development of LMSs is discussed along with their role in higher education from a networked learning perspective.